2018
DOI: 10.1007/s41999-018-0070-2
|View full text |Cite
|
Sign up to set email alerts
|

Guideline versus non-guideline based management of rectal cancer in octogenarians

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The NCCN and Oncology Branch of the Chinese Medical Association both recommend neoadjuvant therapy for advanced RC. Studies have also shown that hospitals with a high utilization rate of neoadjuvant therapy are associated with better survival [8][9][10]. However, in this study, only 39.55% (n = 140) of the patients received standard neoadjuvant therapy, which implies that current guidelines cannot be carried out easily for patients with clinical T4 RC.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The NCCN and Oncology Branch of the Chinese Medical Association both recommend neoadjuvant therapy for advanced RC. Studies have also shown that hospitals with a high utilization rate of neoadjuvant therapy are associated with better survival [8][9][10]. However, in this study, only 39.55% (n = 140) of the patients received standard neoadjuvant therapy, which implies that current guidelines cannot be carried out easily for patients with clinical T4 RC.…”
Section: Discussionmentioning
confidence: 67%
“…However, previous studies have shown that receiving guideline-based neoadjuvant radiotherapy resulted in better survival benefits within 5 years. The analysis of data from two teaching hospitals in the southern part of the Netherlands between 2008 and 2015 showed that patients treated according to the guidelines had better survival 18 months after diagnosis (80 versus 56%) [10]. Eid, Y. conducted a trial in 2019 that found compliance with the relevant guidelines improved the quality of the multidisciplinary management of patients who underwent curative surgery for subperitoneal RC [9].…”
Section: Discussionmentioning
confidence: 99%
“…Although somewhat higher, still only 27.5% of octogenarians with localized disease received adjuvant or neo-adjuvant chemotherapy in a series of colorectal cancer patients treated in Israel [ 14 ]. Treatment of localized rectal cancer was adherent to guidelines in only 54% of octogenarians in a retrospective series from the Netherlands [ 41 ]. Patients treated according to guidelines had an 18-month survival of 80% versus 56% for octogenarians not treated according to guidelines.…”
Section: Treatments Of Colorectal Cancers In Octogenarians and Older ...mentioning
confidence: 99%